Positive electrode active material for non-aqueous electrolyte secondary battery and method for producing precursor thereof
By cleaning the nickel-manganese composite hydroxide particles with carbonate aqueous solution during the manufacturing process of lithium nickel-manganese composite oxide, the problem of impurity residue in lithium nickel-manganese composite oxide is solved, and efficient and safe battery performance is achieved.
Patent Information
- Application Number
- CN202110473072.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2014-03-28
- Filing Date
- 2015-03-12
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2035-03-12
AI Technical Summary
The existing lithium nickel-manganese composite oxides contain impurities such as sulfate and chlorine derived from raw materials, resulting in an increase in the irreversible capacity of the battery, safety problems, and the residue of impurities during the manufacturing process may lead to equipment corrosion and short circuit.
By cleaning with carbonate aqueous solution, the impurity content in the nickel-manganese composite hydroxide particles, especially sulfate and chlorine, is reduced, and nickel-cobalt-manganese composite hydroxide precursors with fewer impurities are produced, and are used to prepare highly efficient lithium nickel-manganese composite oxide positive electrode active substances.
It realizes the reduction of the irreversible capacity of the battery, improves the Coulomb efficiency and reaction resistance, reduces the corrosion risk of manufacturing equipment, and improves the overall performance of the battery.
Smart Images

Figure CN113247967B_ABST
Abstract
Description
[0001] The present application is a divisional application of the application date of March 12, 2015, the application number of 201580016512X, and the invention name of the precursor of positive electrode active material for non-aqueous electrolyte secondary battery and its manufacturing method, and the positive electrode active material for non-aqueous electrolyte secondary battery and its manufacturing method. Technical Field
[0002] The present invention relates to a precursor of a positive electrode active material for a non-aqueous electrolyte secondary battery and a method for producing the same, and to a positive electrode active material for a non-aqueous electrolyte secondary battery and a method for producing the same. Background Art
[0003] In recent years, with the popularity of portable devices such as mobile phones and laptops, there is a strong desire for the development of secondary batteries with high energy density, small size and light weight. As secondary batteries that meet such requirements, lithium ion secondary batteries using lithium, lithium alloys, metal oxides or carbon as negative electrode active materials are actively being researched and developed.
[0004] Lithium-ion secondary batteries that use lithium composite oxides, especially lithium cobalt composite oxides (LiCoO2) which are relatively easy to synthesize, as positive electrode active materials can obtain high voltages of 4V, so they are expected to be practically used as batteries with high energy density. In batteries using lithium cobalt composite oxides, many developments have been carried out so far to obtain excellent initial capacity characteristics and cycle characteristics, and various results have been achieved.
[0005] However, lithium cobalt composite oxides use rare and expensive cobalt compounds as raw materials, which increases the cost, and cheaper positive electrode active materials are expected to be used instead. Reducing the cost of positive electrode active materials and manufacturing cheaper lithium ion secondary batteries are of great industrial significance in the miniaturization and lightweighting of currently popular portable devices.
[0006] As new materials for positive electrode active materials for lithium ion secondary batteries, there are lithium manganese composite oxide (LiMn2O4) using manganese which is cheaper than cobalt and lithium nickel composite oxide (LiNiO2) using nickel.
[0007] Lithium manganese composite oxides are cheap raw materials and have excellent thermal stability, so they can be said to be a powerful alternative material for lithium cobalt composite oxides. However, the theoretical capacity of lithium manganese composite oxides is only about half of that of LiCoO2, so it is difficult to adapt to the increasing demand for high-capacity lithium-ion secondary batteries. In addition, lithium nickel composite oxides have worse cycle characteristics than lithium cobalt composite oxides, and are more likely to damage battery performance when used or stored in a high-temperature environment.
[0008] On the other hand, lithium nickel manganese composite oxides, which have the same degree of thermal stability and durability as lithium cobalt composite oxides, are strong candidates as substitutes for lithium cobalt composite oxides. For example, Patent Document 1 proposes that as a precursor of a positive electrode active material containing lithium manganese nickel composite oxide, composite hydroxide particles with a manganese:nickel ratio of 1:1 are substantially prepared, with an average particle size of 5 to 15 μm, a tap density of 0.6 to 1.4 g / ml, a bulk density of 0.4 to 1.0 g / ml, and a specific surface area of 20 to 55 m 2 / g, and containing 0.25 to 0.45% by mass of sulfate. In addition, as a method for producing the same, it is disclosed that the degree of oxidation of manganese ions is controlled within a certain range, and a mixed aqueous solution of a manganese salt and a nickel salt having a substantially 1:1 atomic ratio of manganese to nickel is reacted with an alkaline solution under appropriate stirring conditions in an aqueous solution with a pH value of 9 to 13 in the presence of a complexing agent, so that the generated particles are coprecipitated.
[0009] In addition, in order to improve the cycle characteristics and output characteristics, a positive electrode active material with controlled particle structure is also proposed. For example, patent document 2 discloses a plurality of primary particles aggregated to form a roughly spherical secondary particle, the average particle size of the secondary particle exceeds 7 μm and is less than 15 μm, and the average particle size [(d90-d10) / average particle size] of the index indicating the particle size distribution width is less than 0.55. The average particle size obtained by using the nickel composite hydroxide exceeds 8 μm and is less than 16 μm, and the average particle size [(d90-d10) / average particle size] of the index indicating the particle size distribution width is less than 0.60, and the positive electrode active material for a non-aqueous electrolyte secondary battery is composed of a hollow portion existing in the outer shell and the inner shell.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2004-210560
[0013] Patent Document 2: International Publication No. 2012 / 169274 Summary of the invention
[0014] Problem that the invention aims to solve
[0015] However, although the structure of the particles of manganese-nickel composite oxide is studied in Patent Document 1, the reduction of impurities is not studied. The lithium-nickel-manganese composite oxide obtained by the previous manufacturing method contains impurities such as sulfate and chlorine from the raw materials that do not contribute to the charge and discharge reaction. Therefore, when forming a battery, the negative electrode material equivalent to the irreversible capacity of the positive electrode material cannot be used additionally for the battery. As a result, the capacity per weight and per volume of the entire battery becomes smaller, and the excess lithium accumulated in the negative electrode as irreversible capacity also has problems from the safety aspect.
[0016] Furthermore, the residual chlorine as impurities may volatilize during the firing process, corrode the firing furnace and peripheral equipment, and generate metallic foreign matter contaminants in the product that may cause short circuits in the battery, and it is required to reduce it as much as possible.
[0017] In addition, in the positive electrode active material with a hollow structure described in Patent Document 2, in its manufacturing process, a neutralization crystallization of a nickel composite hydroxide including a nucleation process for generating a particle nucleus and a particle growth process for growing the generated nucleus is performed, and the particle growth process is crystallized at a relatively low pH value, so there is a problem that impurities such as sulfate and chlorine are easy to remain. In addition, fine particles are crystallized in the nucleation process, so in the subsequent particle growth process, even if the particles are allowed to grow, high density cannot be obtained, and impurities become easy to remain inside the particles.
[0018] In view of the above-mentioned problems of the prior art, the present invention aims to provide a precursor of a positive electrode active material and a method for producing the same, which can reduce the amount of impurities, provide a high capacity, a small irreversible capacity, and excellent coulombic efficiency and reaction resistance for a non-aqueous electrolyte secondary battery.
[0019] Solutions for solving problems
[0020] In order to solve the above-mentioned problems, the present inventors conducted in-depth research on reducing the amount of impurities, and found that by washing a nickel-manganese composite hydroxide having a specific composition and structure with a carbonate aqueous solution, a nickel-cobalt-manganese composite hydroxide with few impurities can be obtained. By using it as a precursor, a positive electrode active material with few impurities and excellent battery characteristics can be manufactured, thereby completing the present invention.
[0021] That is, the method for manufacturing a precursor of a positive electrode active material for a non-aqueous electrolyte secondary battery of the present invention is characterized in that the precursor of the positive electrode active material for a non-aqueous electrolyte secondary battery has a hollow structure or a porous structure, and the nickel-manganese composite hydroxide particles represented by the following general formula (1) and having a void structure inside the particles are washed with a carbonate aqueous solution having a carbonate concentration of 0.1 mol / L or more to obtain the precursor.
[0022] General formula: Ni xCo y Mn z M t (OH)2···(1)
[0023] (wherein, 0.2 ≤ x ≤ 0.8, 0 ≤ y < 0.3, 0.07 < z ≤ 0.8, 0 ≤ t ≤ 0.1, x + y + z + t = 1, and M is at least one element selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta, and W)
[0024] In addition, the porosity of the aforementioned nickel-manganese composite hydroxide particles measured in cross-sectional observation is preferably 15% or more.
[0025] In addition, the aforementioned aqueous carbonate solution is an aqueous solution of at least one selected from potassium carbonate, sodium carbonate, potassium hydrogencarbonate, and sodium hydrogencarbonate, and the pH of the aforementioned aqueous carbonate solution is preferably 11.2 or more.
[0026] In addition, the aforementioned cleaning is preferably performed in the range of a liquid temperature of 15 to 50°C.
[0027] In addition, the aforementioned nickel-manganese composite hydroxide particles are obtained as follows: A mixed aqueous solution containing nickel, manganese, and, if necessary, cobalt and the aforementioned metal compound M, and an aqueous solution containing an ammonium ion donor are supplied to a heated reaction tank. At this time, an aqueous solution of an alkali metal hydroxide in an amount sufficient to keep the reaction solution alkaline is appropriately supplied to the reaction solution, and neutralization crystallization is performed to obtain the aforementioned nickel-manganese composite hydroxide particles. In the aforementioned neutralization crystallization, preferably, by controlling the pH value of the aforementioned reaction solution, a nucleation step for nucleation and a particle growth step for growing the aforementioned generated nuclei are performed separately.
[0028] The pH value in the aforementioned nucleation step is preferably controlled to be 12.0 to 14.0 based on a liquid temperature of 25°C, and the pH value in the aforementioned particle growth step is controlled to be 10.5 to 12.5 based on a liquid temperature of 25°C and a value lower than the pH value in the nucleation step.
[0029] In addition, the aforementioned mixed aqueous solution preferably contains at least one chloride of nickel, manganese, and cobalt.
[0030] A precursor of a positive electrode active material for a non-aqueous electrolyte secondary battery according to the present invention, characterized in that the precursor of the positive electrode active material for a non-aqueous electrolyte secondary battery has a hollow structure or a porous structure, contains nickel-manganese composite hydroxide particles represented by the following general formula (1) and having a void structure inside the particles, and has a sulfate content of 0.4% by mass or less and a sodium content of 0.035% by mass or less.
[0031] General formula: Ni x Co y Mnz M t (OH)2···(1)
[0032] (where 0.2 ≤ x ≤ 0.8, 0 ≤ y < 0.3, 0.07 < z ≤ 0.8, 0 ≤ t ≤ 0.1, x + y + z + t = 1, and M is at least one element selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta, and W)
[0033] In addition, the chlorine content of the precursor of the positive electrode active material for the non-aqueous electrolyte secondary battery is preferably 0.1% by mass or less.
[0034] The method for manufacturing a positive electrode active material for a non-aqueous electrolyte secondary battery according to the present invention is characterized in that the positive electrode active material for a non-aqueous electrolyte secondary battery contains a lithium nickel manganese composite oxide represented by the following general formula (2) and having a hollow structure or a porous structure.
[0035] The manufacturing method includes the following steps: a mixing step of mixing the precursor of the positive electrode active material for the non-aqueous electrolyte secondary battery with a lithium compound to obtain a lithium mixture; and a firing step of firing the lithium mixture in an oxidizing atmosphere in the range of 800 to 1100 °C to obtain a lithium nickel manganese composite oxide.
[0036] General formula: Li a Ni x Co y Mn z M t O2···(2)
[0037] (where 0.95 ≤ a ≤ 1.20, 0.2 ≤ x ≤ 0.8, 0 ≤ y < 0.3, 0.07 < z ≤ 0.8, 0 ≤ t ≤ 0.1, x + y + z + t = 1, and M is at least one element selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta, and W)
[0038] In addition, the lithium compound is preferably at least one selected from the group consisting of lithium hydroxide, hydroxyoxide, oxide, carbonate, nitrate, and halide.
[0039] The positive electrode active material for a non-aqueous electrolyte secondary battery according to the present invention is characterized in that it contains lithium nickel manganese composite oxide particles represented by the following general formula (2) and having a hollow structure or a porous structure, the sulfate content is 0.4% by mass or less, and the sodium content is 0.035% by mass or less.
[0040] General formula: Li a Ni x Co y Mnz M t O2···(2)
[0041] (wherein, 0.95 ≤ a ≤ 1.20, 0.2 ≤ x ≤ 0.8, 0 ≤ y < 0.3, 0.07 < z ≤ 0.8, 0 ≤ t ≤ 0.1, x + y + z + t = 1, and M is at least one element selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta, and W)
[0042] In addition, the positive electrode active material for non-aqueous electrolyte secondary batteries preferably has a chlorine content of 0.05% by mass or less.
[0043] Furthermore, the non-aqueous electrolyte secondary battery of the present invention uses the aforementioned positive electrode active material for non-aqueous electrolyte secondary batteries.
[0044] Effects of the Invention
[0045] The present invention provides a precursor of a positive electrode active material for non-aqueous electrolyte secondary batteries and a method for manufacturing the same, which can obtain a positive electrode active material with a small amount of residual impurities, high capacity, small irreversible capacity, excellent coulomb efficiency, and reaction resistance. The manufacturing method of this precursor is easy to improve productivity and has a small amount of impurities that corrode the firing furnace and peripheral equipment, etc., so it can reduce damage to manufacturing equipment. Furthermore, the manufacturing method of the positive electrode active material of the present invention can easily obtain a positive electrode active material for non-aqueous electrolyte secondary batteries with high capacity, small irreversible capacity, excellent coulomb efficiency, and reaction resistance, and its industrial value is extremely high. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 It is a cross-sectional view of a button battery used in battery evaluation. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0047] Hereinafter, a precursor of a positive electrode active material for non-aqueous electrolyte secondary batteries, a method for manufacturing the same, and a method for manufacturing a positive electrode active material for non-aqueous electrolyte secondary batteries using the precursor will be described in detail. It should be noted that the embodiments described below are merely illustrative, and the present invention can be implemented in various modified and improved forms based on the following embodiments and the knowledge of those skilled in the art.
[0048] 1. Method for Manufacturing a Precursor of a Positive Electrode Active Material for Non-Aqueous Electrolyte Secondary Batteries
[0049] (1) Composition of Nickel-Manganese Composite Hydroxide Particles
[0050] A method for manufacturing a precursor of a positive electrode active material for a non-aqueous electrolyte secondary battery (hereinafter, also simply referred to as "precursor"), characterized in that nickel-manganese composite hydroxide particles represented by the following general formula (1) and having a void structure inside the particles (hereinafter, also simply referred to as "composite hydroxide particles") are washed with an aqueous carbonate solution having a carbonate concentration of 0.1 mol / L or more to obtain a precursor.
[0051] General formula: Ni x Co y Mn z M t (OH)2···(1)
[0052] (where 0.2 ≤ x ≤ 0.8, 0 ≤ y < 0.3, 0.07 < z ≤ 0.8, 0 ≤ t ≤ 0.1, x + y + z + t = 1, and M is at least one element selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta, and W)
[0053] X, which represents the content of nickel in the composite hydroxide particles, is 0.2 ≤ x ≤ 0.8, preferably 0.35 ≤ x ≤ 0.6, and more preferably 0.4 ≤ x ≤ 0.6. By using composite hydroxide particles having a nickel content within the above range as a precursor, a positive electrode active material having excellent discharge capacity can be obtained.
[0054] Y, which represents the content of cobalt in the composite hydroxide particles, is 0 ≤ y < 0.3, preferably 0.1 ≤ y ≤ 0.25, and more preferably 0.1 ≤ y ≤ 0.2. By using composite hydroxide particles having a cobalt content within the above range as a precursor, a positive electrode active material having excellent discharge capacity and cycle characteristics can be obtained.
[0055] Z, which represents the content of manganese in the composite hydroxide particles, is 0.07 < z ≤ 0.8, preferably 0.1 ≤ z ≤ 0.6, and more preferably 0.1 ≤ z ≤ 0.5. By using composite hydroxide particles having a manganese content within the above range as a precursor, a positive electrode active material having excellent cycle characteristics and thermal stability can be obtained.
[0056] In addition, t, which represents the content of element M in the composite hydroxide particles, is 0 ≤ t ≤ 0.1, preferably 0 ≤ t ≤ 0.07, and more preferably 0 ≤ t ≤ 0.05. By using composite hydroxide particles having an M content within the above range as a precursor, a positive electrode active material having excellent discharge capacity, cycle characteristics, and thermal stability can be obtained.
[0057] It should be noted that the composition ratios of nickel, cobalt, manganese, and element M in the composite hydroxide particles (precursor) are also maintained in the lithium nickel manganese composite oxide particles (positive electrode active material) described later.
[0058] (2) Internal structure of nickel-manganese composite hydroxide particles
[0059] The composite hydroxide particles used in this embodiment have a void structure inside the particles, and lithium nickel manganese composite oxide particles (hereinafter, also simply referred to as "composite oxide particles") having a hollow structure or a porous structure can be obtained. The positive electrode active material containing composite oxide particles having a hollow structure or a porous structure increases the contact area with the electrolyte, and thus has excellent output characteristics.
[0060] Here, "composite hydroxide particles having a void structure inside the particles" refers to particles having a structure containing a plurality of voids between the primary particles constituting the secondary particles, and after the sintering process described later, composite hydroxide particles of a positive electrode active material having a hollow structure or a porous structure can be obtained. For example, composite hydroxide particles having a plurality of voids between fine primary particles as disclosed in Patent Document 2, etc., can be listed, which are composed of secondary particles having a central portion containing fine primary particles, and having a peripheral portion containing primary particles larger than the fine primary particles on the outside of the central portion. In addition, it can be a central portion containing a plurality of fine primary particles in the composite hydroxide particles, or it can be a structure in which the composite hydroxide particles as a whole contain a plurality of voids between the primary particles. In addition, these listed structures can be composite structures. On the other hand, the "hollow structure or porous structure" of the positive electrode active material refers to a structure consisting of a hollow portion consisting of a space containing the central portion of the particle and an outer shell portion on its outside, or a structure in which the voids in the particles are dispersed throughout the particles.
[0061] The void structure, hollow structure, or porous structure can be confirmed by cross-sectional observation of the composite hydroxide particles / composite oxide particles using a scanning electron microscope.
[0062] In addition, for the composite hydroxide particles / composite oxide particles having the above-mentioned void structure, hollow structure or porous structure, the void ratio measured in the cross-section observation of these particles is 5% or more, preferably 15% or more, and more preferably 15 to 85%. Thus, the bulk density of the obtained positive electrode active material is not reduced too much, and the contact area between the positive electrode active material and the electrolyte can be sufficient.
[0063] The porosity can be measured by observing any cross section of the composite hydroxide particles / composite oxide particles using a scanning electron microscope and analyzing the image. For example, after a plurality of composite hydroxide particles / composite oxide particles are embedded in a resin, etc., and their particles are processed by a cross-section polisher to be in a state where cross-section observation can be performed, the void portion (the hollow portion of the hollow structure or the void portion of the porous structure) in the above-mentioned secondary particles can be measured as black, and the dense portion (the shell portion forming the hollow structure, the primary particle cross section of the void structure / porous structure) in the secondary particle outline can be measured as white, and the porosity can be calculated by calculating the area of [black portion / (black portion+white portion)] for any 20 or more particles.
[0064] (3) Method for producing nickel-manganese composite hydroxide particles
[0065] The method for producing the composite hydroxide particles used in the present embodiment is not particularly limited as long as a composite hydroxide that satisfies the above formula (1) and has a void structure inside the particles can be obtained, and a conventionally known method can be used.
[0066] For example, there can be cited a method in which a mixed aqueous solution of a metal compound containing nickel and manganese and, as required, cobalt and at least one element M selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta and W and an aqueous solution containing an ammonium ion donor are supplied to a heated reaction tank, and at this time, an aqueous solution of an alkali metal hydroxide in an amount sufficient to keep the reaction solution alkaline is appropriately supplied to carry out neutralization and crystallization.
[0067] In addition, during the neutralization crystallization, it is preferred to control the pH value of the reaction solution to separately perform a nucleation step for nucleation and a particle growth step for nucleation growth, thereby obtaining nickel-manganese composite hydroxide particles having a void structure and including secondary particles formed by aggregation of primary particles.
[0068] Here, carrying out the nucleation process and the particle growth process separately means that: as shown in the previous continuous crystallization method, the nucleation reaction and the particle growth reaction do not occur at the same time in the same layer, and the period when the nucleation reaction (nucleation process) mainly occurs is clearly separated from the period when the particle growth reaction (particle growth process) mainly occurs.
[0069] Furthermore, it is preferred to control the pH value in the nucleation step to 12.0 to 14.0 based on a liquid temperature of 25°C, and to control the pH value in the particle growth step to 10.5 to 12.5 based on a liquid temperature of 25°C, which is lower than the pH value in the nucleation step, from the viewpoint of uniformity and stability of particle size, etc. It is more preferred to control the pH value in the particle growth step to a value that is 0.5 or more lower than the pH value in the nucleation step.
[0070] In addition, with regard to the atmospheric atmosphere in the nucleation process and the particle growth process, for example, it is preferred to set the nucleation process to an oxidizing atmosphere with an oxygen concentration exceeding 1 volume %, and to switch from the aforementioned oxidizing atmosphere to a mixed atmosphere of oxygen and an inert gas with an oxygen concentration of less than 1 volume % in the middle of the particle growth process.
[0071] That is, by setting the nucleation process and the initial part of the particle growth process to an oxidizing atmosphere, a central part containing a plurality of fine voids including fine primary particles can be formed, and in the subsequent particle growth process, the oxidizing atmosphere is switched to an atmosphere in the range of weak oxidizing to non-oxidizing, thereby forming a particle structure including an outer shell part having plate-like primary particles larger than the fine primary particles on the outside of the central part. In the composite hydroxide particles having such a particle structure, the fine primary particles in the central part are absorbed by the outer shell part during the calcination process when obtaining the positive electrode active material, and become composite oxide particles having a hollow structure.
[0072] Furthermore, by adjusting the timing of switching the atmosphere in the particle growth step, the size of the hollow portion of the composite oxide particles having a hollow structure can be controlled.
[0073] In addition, by setting both the nucleation step and the particle growth step to an atmosphere in the range of weak oxidizing to non-oxidizing, that is, a mixed atmosphere of oxygen and an inert gas with an oxygen concentration of 1 volume % or less, the primary particles formed in the nucleation step grow, and composite hydroxide particles having a void structure in which the particles as a whole have a plurality of voids between the primary particles can be obtained. For composite hydroxide particles having such a particle structure, the residual voids become larger when the primary particles are sintered and grown in the sintering step when obtaining the positive electrode active material, and thus become lithium nickel composite oxide particles (positive electrode active material) having a porous structure.
[0074] The metal compounds containing nickel, manganese and cobalt are not particularly limited, and for example, sulfides, nitrates, chlorides, etc. can be used. Among them, sulfides or chlorides are preferably used from the viewpoint of ease of wastewater treatment and environmental burden. In addition, from the viewpoint of environmental burden, it is particularly preferred to use a chloride of at least one of nickel, manganese and cobalt.
[0075] There is no particular limitation on the metal compound containing at least one element M among Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta and W. For example, magnesium sulfate, calcium sulfate, sodium aluminate, aluminum sulfate, titanium sulfate, ammonium pertitanate, potassium titanium oxalate, vanadium sulfate, ammonium vanadate, chromium sulfate, potassium chromate, zirconium sulfate, zirconium nitrate, ammonium molybdate, sodium tungstate, ammonium tungstate and the like can be used.
[0076] The alkali metal hydroxide is not particularly limited, and a known alkali metal hydroxide can be used. For example, sodium hydroxide, potassium hydroxide, etc. can be used.
[0077] The ammonium ion donor is not particularly limited, and for example, ammonia, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium fluoride, etc. can be used.
[0078] The ammonium ion concentration in the nucleation step and the particle growth step is preferably 3 to 25 g / L, more preferably 5 to 20 g / L, from the viewpoint of maintaining a constant metal ion concentration and stabilizing the shape and particle size.
[0079] (4) Cleaning with carbonate solution
[0080] For the manufacturing method of the precursor of the present embodiment, the nickel-manganese composite hydroxide particles having a void structure inside the particles are washed with a carbonate aqueous solution having a concentration of 0.1 mol / L or more, preferably 0.15 to 2.00 mol / L, and more preferably 0.20 to 1.50 mol / L to obtain a precursor. By using a carbonate aqueous solution having a concentration of 0.1 mol / L or more during washing, impurities in the composite hydroxide particles, especially sulfate, chlorine, etc., can be efficiently removed by ion exchange with carbonate ions in the carbonate aqueous solution. In particular, in the case of hydroxide particles having the above-mentioned void structure, it is difficult to remove the aforementioned impurities inside the particles when washing with an aqueous solution of an alkali metal such as water or sodium hydroxide used in the past, and washing with a carbonate aqueous solution is effective.
[0081] During washing, the pH is preferably 11.2 or higher, more preferably 11.5 or higher at 25°C. By setting the pH to 11.2 or higher, sulfate and chlorine that form acids can be removed more efficiently. The upper limit of the pH is not particularly limited, but since a carbonate aqueous solution is used, the upper limit of the pH at 25°C is about 12.5.
[0082] The carbonate aqueous solution is preferably an aqueous solution of at least one selected from potassium carbonate (K2CO3), sodium carbonate (Na2CO3), potassium bicarbonate and sodium bicarbonate. Lithium carbonate, calcium carbonate and barium carbonate have low solubility in water, so sometimes it is not possible to obtain an aqueous solution containing a sufficient amount of them.
[0083] In addition, for example, when sodium carbonate is used as the carbonate, the concentration of the aqueous solution is preferably 0.2 mol / L or more, more preferably 0.25 to 1.50 mol / L. Sodium carbonate has high solubility in water, so the concentration of the aqueous solution is set to 0.2 mol / L or more, thereby more efficiently removing impurities such as sulfate and chlorine.
[0084] The water temperature of the carbonate aqueous solution is preferably 15° C. to 50° C. When the water temperature is within the above range, the ion exchange reaction becomes active and impurities are removed efficiently.
[0085] As the liquid volume of the carbonate aqueous solution used in cleaning, as long as the sulfate content of the composite hydroxide particles can be fully cleaned in a manner of 0.4 mass % or less and the sodium content of 0.035 mass % or less, there is no particular limitation. For example, the liquid volume in the case of using sodium carbonate aqueous solution is preferably 1000 mL or more, more preferably 2000 to 5000 mL relative to 1000 g of nickel-manganese composite hydroxide. When it is less than 1000 mL, sometimes the impurity ions and carbonate ions are not fully replaced and the cleaning effect cannot be fully obtained.
[0086] The washing time with the carbonate aqueous solution is not particularly limited as long as the composite hydroxide particles can be sufficiently washed so that the sulfate content is 0.4 mass % or less and the sodium content is 0.035 mass % or less, but is usually 0.5 to 2 hours.
[0087] As a cleaning method, 1) nickel manganese composite hydroxide particles are added to a carbonate aqueous solution to form a slurry, and a commonly used cleaning method such as filtering after cleaning, or 2) a slurry containing composite hydroxide particles generated by neutralization and crystallization can be supplied to a filter such as a filter press, and the carbonate aqueous solution is passed through a liquid and washed with water. The removal efficiency of impurities in the water washing is high, and in addition, filtering and washing can be continuously performed in the same equipment, and the productivity is high, so it is preferred.
[0088] After washing with a carbonate aqueous solution, it is then washed with pure water as necessary. In order to remove cationic impurities such as sodium, it is preferably washed with pure water.
[0089] The washing with pure water can be carried out by a commonly used method. When washing with the carbonate aqueous solution is carried out, it is preferable to continuously wash with pure water after washing with the carbonate aqueous solution.
[0090] 2. Precursor of positive electrode active material for non-aqueous electrolyte secondary battery
[0091] The precursor of the positive electrode active material for the non-aqueous electrolyte secondary battery according to the present embodiment contains nickel-manganese composite hydroxide particles represented by the following general formula (1) and having a void structure, with a sulfate content of 0.4% by mass or less and a sodium content of 0.035% by mass or less.
[0092] General formula: Ni x Co y Mn z M t (OH)2···(1)
[0093] (where 0.2 ≤ x ≤ 0.8, 0 ≤ y < 0.3, 0.07 < z ≤ 0.8, 0 ≤ t ≤ 0.1, x + y + z + t = 1, and M is at least one element selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta, and W)
[0094] The sulfate contained in the precursor does not decrease even in the firing step in the production of the positive electrode active material and remains in the positive electrode active material. Therefore, it is necessary to sufficiently reduce it in advance in the precursor. By setting the sulfate content to 0.4% by mass or less, preferably 0.35% by mass or less, and more preferably 0.3% by mass or less, the sulfate content of the obtained positive electrode active material can also be made 0.4% by mass or less, preferably 0.35% by mass or less.
[0095] Regarding the content of sodium in the precursor, it does not decrease even in the firing step performed when manufacturing the positive electrode active material, but sometimes increases due to the lithium salt as the mixed raw material. Therefore, it is necessary to sufficiently reduce the sodium content in the precursor in advance so as to become 0.035% by mass or less, preferably 0.030% by mass or less, and more preferably 0.028% by mass or less.
[0096] Furthermore, the chlorine content in the precursor is preferably 0.1% by mass or less, more preferably 0.05% by mass or less, and further preferably 0.02% by mass or less. Although chlorine has less influence on the positive electrode active material due to sulfate, it has an adverse effect on the firing furnace, etc. during the production of the positive electrode active material, and it is preferably sufficiently reduced in the precursor in advance.
[0097] The contents of sulfate, sodium, and chlorine in the precursor can be made within the above ranges by appropriately adjusting the concentration, amount, temperature, etc. of the carbonate aqueous solution when washing the nickel-manganese composite hydroxide with the carbonate aqueous solution.
[0098] 3. Method for manufacturing a positive electrode active material for a non-aqueous electrolyte secondary battery
[0099] The manufacturing method of the positive electrode active material for a non-aqueous electrolyte secondary battery according to this embodiment includes the following steps: 1) a mixing step of mixing the precursor with a lithium compound to obtain a lithium mixture; 2) a firing step of firing the aforementioned lithium mixture in an oxidizing atmosphere in the range of 800 to 1100 °C to obtain lithium nickel manganese composite oxide particles represented by the following general formula (2).
[0100] General formula: Li a Ni x Co y Mn z M t O2···(2)
[0101] (where 0.95 ≤ a ≤ 1.20, 0.2 ≤ x ≤ 0.8, 0 ≤ y < 0.3, 0.07 < z ≤ 0.8, 0 ≤ t ≤ 0.1, x + y + z + t = 1, and M is at least one element selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta, and W)
[0102] Hereinafter, each step will be described.
[0103] (1) Mixing step
[0104] The mixing step is a step of mixing the precursor with a lithium compound to obtain a lithium mixture.
[0105] As the mixing ratio of the precursor and the lithium compound, it is preferable to adjust the molar ratio (Li / Me) of lithium (Li) to a metal element (Me) other than lithium to be 0.95 to 1.20, preferably 1.00 to 1.15. That is, the molar ratio (Li / Me) in the lithium mixture is mixed in such a way as to be the same as the molar ratio (Li / Me) in the positive electrode active material of this embodiment. This is because the molar ratio (Li / Me) does not change before and after the firing step, and the molar ratio (Li / Me) mixed in this mixing step is the molar ratio (Li / Me) in the positive electrode active material. It should be noted that the value of a in the general formula (2) is such that the composition ratio (x + y + z + t) of Me is 1, so it is the same value as the molar ratio (Li / Me) in the positive electrode active material.
[0106] When the molar ratio (Li / Me) of the obtained positive electrode active material is less than 0.95, it is the cause of a significant reduction in the battery capacity during charge and discharge cycles. On the other hand, when it exceeds 1.20, the internal resistance of the positive electrode when the battery is fabricated becomes large.
[0107] The lithium compound is not particularly limited. For example, at least one selected from the group consisting of lithium hydroxide, hydroxyoxide, oxide, carbonate, nitrate, and halide can be used, and lithium hydroxide and / or carbonate is more preferably used.
[0108] For the above mixing, a dry mixer such as a V-type mixer or a mixing granulator or the like can be used.
[0109] Furthermore, a calcination step may be added before the mixing step.
[0110] The precursor may be mixed with the lithium compound in the state of a composite hydroxide, and a calcination step may be added before the mixing step to remove residual moisture in the precursor, or the composite hydroxide may be further converted into a nickel-manganese composite oxide.
[0111] The calcination step can further easily control the ratio of lithium to metal elements other than lithium, stabilize the composition of the obtained lithium nickel manganese composite oxide particles, and suppress the inhomogeneity of the composition during calcination. For example, the calcination step is performed at 150 to 1000° C. in an oxidizing atmosphere. In addition, in order to obtain the nickel manganese composite oxide, it is preferably calcined at a temperature of 400 to 900° C., more preferably 400 to 800° C.
[0112] At this time, when the calcination temperature is lower than 150°C, the residual water in the precursor may not be fully removed. On the other hand, when the calcination temperature exceeds 1000°C, the primary particles constituting the particles grow violently, and the reaction area of the precursor side after calcination in the subsequent production of lithium nickel manganese composite oxide particles is too small, so the reactivity with lithium is sometimes reduced, and the crystallinity of the lithium nickel manganese composite oxide is reduced. In addition, when the calcination temperature is 300°C or less, it can be implemented while being dried in the crystallization step of obtaining composite hydroxide particles.
[0113] (2) Firing process
[0114] This is a process of calcining the obtained lithium mixture in an oxidizing atmosphere at a temperature in the range of 800 to 1100°C, preferably in the range of 850 to 1050°C, and more preferably in the range of 900 to 1000°C. That is, when heat-treated at a temperature exceeding 800°C, a lithium nickel manganese composite oxide is generated, but when it is below 800°C, the crystallization is incomplete and the structure is unstable, and the structure is easily destroyed due to phase transition during charge and discharge. On the other hand, when it exceeds 1100°C, abnormal grain growth, collapse of the layered structure, and reduction in specific surface area occur, so that insertion and removal of lithium ions become difficult.
[0115] It should be noted that in the firing process, when the temperature rises above 800°C, the nickel-manganese composite hydroxide changes into the form of a composite oxide, and the reaction with the lithium compound ends approximately at around 700°C. Therefore, the firing up to 700°C and the firing above 700°C can be carried out in different devices and processes respectively. By dividing it into two processes, gas components such as water vapor and carbon dioxide generated in the reaction between the nickel-manganese composite hydroxide and the lithium compound will not be introduced into the firing above 700°C for improving crystallinity, and composite hydroxide particles with higher crystallinity can be obtained.
[0116] In addition, in order to remove the crystal water of the lithium compound, etc., and to carry out a uniform reaction in the temperature range for crystal growth, pre-firing is carried out, for example, at a temperature in the range of 600 - 900°C and lower than the firing temperature for 1 hour or more before firing.
[0117] In the above-mentioned firing, firing furnaces such as electric furnaces, kilns, tubular furnaces, pusher furnaces, etc. with a gas atmosphere having an oxygen concentration of 20 mass% or more, such as a dry air atmosphere adjusted to an oxygen atmosphere and subjected to dehumidification and decarbonation treatment, can be used.
[0118] Using the precursor of this embodiment as a raw material, by using the above manufacturing method, a positive electrode active material for a non-aqueous electrolyte secondary battery containing lithium nickel manganese composite oxide particles with a sulfate content of 0.4 mass% or less, a sodium content of 0.035 mass% or less, and preferably a chlorine content of 0.05 mass% or less can be obtained.
[0119] 4. Positive Electrode Active Material for Non-Aqueous Electrolyte Secondary Battery
[0120] The positive electrode active material for a non-aqueous electrolyte secondary battery of this embodiment contains lithium nickel manganese composite oxide particles represented by the following general formula (2) and having a hollow structure or a porous structure, with a sulfate content of 0.4 mass% or less and a sodium content of 0.035 mass% or less.
[0121] General formula: Li a Ni x Co y Mn z M t O2···(2)
[0122] (where 0.95 ≤ a ≤ 1.20, 0.2 ≤ x ≤ 0.8, 0 ≤ y < 0.3, 0.07 < z ≤ 0.8, 0 ≤ t ≤ 0.1, x + y + z + t = 1, and M is at least one element selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta, and W)
[0123] It should be noted that the values of x, y, z and t in general formula (2) can be the same as the values of x, y, z and t in general formula (1) of the composite hydroxide particles described above, and the value of a can be the same as the value of Li / Me mixed in the above mixing step.
[0124] The sulfate content in the positive electrode active material is 0.4 mass % or less, preferably 0.35 mass % or less, and more preferably 0.3 mass % or less. Thus, when used as a positive electrode active material of a battery, the irreversible capacity can be reduced, the coulomb efficiency can be improved, and a high capacity can be obtained. In addition, the excess lithium accumulated on the negative electrode can also be suppressed, and the safety can also be improved.
[0125] The sodium content in the positive electrode active material is 0.035 mass % or less, preferably 0.030 mass % or less. Sodium is also a substance that increases irreversible capacity like sulfate, and by setting the content to 0.035 mass % or less, the irreversible capacity is reduced when used as a positive electrode active material of a battery, and high coulomb efficiency can be obtained. In addition, the sodium remaining in the positive electrode active material increases the resistance value of the positive electrode active material, so by setting the sodium content to the above range, the output characteristics can be improved.
[0126] Furthermore, chlorine is also a substance that increases the irreversible capacity, and therefore the chlorine content in the positive electrode active material is preferably 0.05 mass % or less, more preferably 0.01 mass % or less, and even more preferably 0.005 mass % or less.
[0127] In addition, the lithium nickel manganese composite oxide particles constituting the positive electrode active material of this embodiment have a hollow structure or a porous structure. As a result, the contact area with the electrolyte can be increased, and a positive electrode active material with excellent output characteristics can be made. Furthermore, in order to improve the output characteristics, the porosity measured in the cross-sectional observation is preferably 15% or more, more preferably 15 to 85%. It should be noted that the particle structure and porosity can be confirmed and obtained by the same method as the aforementioned composite hydroxide particles.
[0128] 5. Non-aqueous electrolyte secondary battery
[0129] The non-aqueous electrolyte secondary battery of the present embodiment can be composed of constituent elements such as a positive electrode, a negative electrode, and a non-aqueous electrolyte solution in the same manner as a general lithium-ion secondary battery. Below, each constituent element is described in detail. It should be noted that the embodiments described below are merely illustrative, and the non-aqueous electrolyte secondary battery of the present invention is based on the following embodiments and can be implemented in various ways of changes and improvements based on the knowledge of those skilled in the art. In addition, the non-aqueous electrolyte secondary battery of the present embodiment is not particularly limited to its use.
[0130] (1) Positive electrode
[0131] The positive electrode mixture for forming the positive electrode and the materials constituting it are described. The above-mentioned powdered positive electrode active material, conductive material, and binder are mixed, and activated carbon and a solvent for the purpose of viscosity adjustment are added as needed, and the mixture is kneaded to make a positive electrode mixture paste. It should be noted that the mixing ratio of the positive electrode mixture can be adjusted according to the performance of the required lithium secondary battery.
[0132] For example, when the total mass of the solid components of the positive electrode mixture excluding the solvent is set to 100 mass%, the content of the positive electrode active material can be set to 60-95 mass%, the content of the conductive material can be set to 1-20 mass%, and the content of the binder can be set to 1-20 mass%, similarly to the positive electrode of a general lithium secondary battery.
[0133] The obtained positive electrode mixture paste is, for example, applied to the surface of a collector made of aluminum foil, dried to disperse the solvent, and pressed by a roller press to increase the electrode density as required to obtain a sheet-like positive electrode. The sheet-like positive electrode thus obtained can be cut into an appropriate size according to the needs of the battery as the purpose, etc. and supplied to the production of the battery. However, the production method of the positive electrode is not limited to the examples, and other methods may also be used.
[0134] As the conductive agent used in the positive electrode, for example, graphite (natural graphite, artificial graphite, expanded graphite, etc.), carbon black materials such as acetylene black and Ketjen black, etc. can be used.
[0135] The binder has the effect of preventing the active material particles from connecting together. For example, fluorine-containing resins such as polyvinylidene fluoride, polytetrafluoroethylene, ethylene propylene diene rubber, and fluororubber, thermoplastic resins such as styrene butadiene, cellulose resins, polyacrylic acid, polypropylene, and polyethylene can be used.
[0136] As required, the positive electrode active material, conductive material, activated carbon, etc. can be dispersed in the positive electrode mixture, and a solvent for dissolving the binder can be added. As the solvent, for example, an organic solvent such as N-methyl-2-pyrrolidone can be used. In addition, activated carbon can be added to the positive electrode mixture in order to increase the electric double layer capacity.
[0137] (2) Negative electrode
[0138] For the negative electrode, a material can be used in which a negative electrode mixture in the form of a paste is applied to the surface of a metal foil collector such as copper, dried, and compressed as needed to increase the electrode density. The paste-like negative electrode mixture is made by mixing a binder with metallic lithium, lithium alloy, or a negative electrode active material that can adsorb and desorb lithium ions and adding an appropriate solvent.
[0139] As the negative electrode active material, for example, a sintered body of an organic compound such as natural graphite, artificial graphite, phenolic resin, or a powder of a carbon material such as coke can be used. At this time, as a binder used in the negative electrode, a fluorine-containing resin such as polyvinylidene fluoride can be used in the same manner as in the positive electrode. In addition, as a solvent for dispersing the negative electrode active material and the binder, an organic solvent such as N-methyl-2-pyrrolidone can be used.
[0140] (3) Separator
[0141] The separator is sandwiched between the positive electrode and the negative electrode. The separator is used to separate the positive electrode and the negative electrode and to retain the electrolyte. A thin film such as polyethylene or polypropylene having many micropores can be used.
[0142] (4) Non-aqueous electrolyte
[0143] Non-aqueous electrolyte is formed by dissolving the lithium salt as supporting salt in an organic solvent. As an organic solvent, for example, cyclic carbonates selected from ethylene carbonate, propylene carbonate, butylene carbonate, trifluoropropylene carbonate, etc. can be used alone, in addition, chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, and then, ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, dimethoxyethane, sulfur compounds such as ethyl methyl sulfone, butane sultone, a kind in phosphorus compounds such as triethyl phosphate, trioctyl phosphate, etc., or mixing two or more uses.
[0144] As supporting salts, LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, etc. and their composite salts can be used.
[0145] Furthermore, the non-aqueous electrolyte may contain a radical scavenger, a surfactant, a flame retardant, and the like.
[0146] (5) Battery shape and structure
[0147] The non-aqueous electrolyte secondary battery can be formed into various shapes such as a cylindrical shape and a stacked shape.
[0148] Even in the case of adopting any shape, the positive electrode and the negative electrode are stacked via a separator to form an electrode body, the electrode body is impregnated with the above-mentioned non-aqueous electrolyte, and a collector lead is used to connect the positive electrode collector and the positive terminal connected to the outside, and the negative electrode collector and the negative terminal connected to the outside, and the battery box is sealed, thereby completing the non-aqueous electrolyte secondary battery.
[0149] Example
[0150] The present invention is further described in detail below by examples and comparative examples, but the present invention is not limited to any of these examples. It should be noted that the analysis method and evaluation method of the metals of the nickel manganese composite hydroxide / lithium nickel manganese composite oxide used in the examples and comparative examples are as follows.
[0151] (1) Composition analysis: Determined by ICP emission spectrometry.
[0152] (2) Sulfate content: Sulfur was quantitatively analyzed by ICP emission spectrometry, and sulfur was completely oxidized to sulfate (SO4 2- ) by multiplying it by a coefficient.
[0153] (3) Na and Cl content: determined by atomic absorption spectrometry.
[0154] (4) Charge and discharge capacity, Coulomb efficiency:
[0155] For the charge and discharge capacity, the button-type battery was placed for about 24 hours after being made. After the open circuit voltage (OCV) stabilized, the positive electrode was charged with a current density of 0.5 mA / cm 2 The capacity at which the battery was charged to a cutoff voltage of 4.3 V and then discharged to a cutoff voltage of 3.0 V after a 1-hour rest was defined as the discharge capacity, and the ratio of the discharge capacity to the charge capacity (discharge capacity / charge capacity) was defined as the coulombic efficiency (%).
[0156] (5) Reaction resistance:
[0157] The reaction resistance was calculated by charging a button-type battery at a charging potential of 4.1 V, using a frequency response analyzer and a potentio / galvano stat (Solartron, 1255B) to create an AC impedance Farquist curve, and fitting calculation was performed using an equivalent circuit to calculate the positive electrode resistance value.
[0158] (Example 1)
[0159] [Manufacturing of Precursor of Positive Electrode Active Material]
[0160] (Nucleation process)
[0161] Water was added to the reaction tank (34 L) until half of the amount was added, and the temperature in the tank was set to 40° C. while stirring at 500 rpm using an inclined blade type stirring paddle. The reaction tank was set to an atmospheric atmosphere (oxygen concentration: 21% by volume). 25% by mass sodium hydroxide aqueous solution and 25% by mass ammonia water were added to the water in the reaction tank in appropriate amounts, and the pH value of the reaction solution in the tank was adjusted to 13.0 at a liquid temperature of 25° C. Furthermore, the ammonia concentration in the reaction solution was adjusted to 15 g / L to prepare a pre-reaction aqueous solution.
[0162] Next, a 2.0 mol / L mixed aqueous solution obtained by dissolving nickel sulfate, manganese sulfate, and cobalt chloride (metal element molar ratio Ni:Co:Mn=50:20:30) in water was added to the pre-reaction aqueous solution in the reaction tank at a rate of 88 ml / min to prepare a reaction aqueous solution. At the same time, 25% by mass ammonia water and 25% by mass sodium hydroxide aqueous solution were added to the reaction aqueous solution at a certain rate, and the pH value was controlled at 13.0 (nucleation pH value) to maintain the ammonia concentration in the reaction aqueous solution (nucleation aqueous solution) at the above value, and crystallization (nucleation) was performed for 15 seconds.
[0163] (Particle Growth Process)
[0164] After the nucleation was completed, when the pH of the reaction aqueous solution reached 11.6 based on a liquid temperature of 25° C., the supply of the 25% by mass sodium hydroxide aqueous solution was only temporarily stopped.
[0165] After the pH value of the reaction aqueous solution reached 11.6, the supply of 25 mass % sodium hydroxide aqueous solution was resumed to the reaction aqueous solution (aqueous solution for particle growth), and the ammonia concentration was maintained at the above value and the pH value was controlled at 11.6 at a liquid temperature of 25° C., and crystallization was continued for 30 minutes to grow particles. Then, the supply of liquid was temporarily stopped, and nitrogen was introduced at 5 L / min until the oxygen concentration in the space of the reaction tank became less than 0.2 volume %. Thereafter, the supply of liquid was resumed, and crystallization was performed for a total of 2 hours from the start of growth.
[0166] When the reaction tank is full of liquid, crystallization is stopped, and stirring is stopped and the reaction tank is left to stand, thereby promoting the precipitation of the product. After that, half of the supernatant is taken out from the reaction tank, crystallization is resumed, and crystallization is completed after 2 hours of crystallization (particle growth: 4 hours in total). The product is then washed with water, filtered, and dried to obtain composite hydroxide particles.
[0167] In the above crystallization, the pH was controlled by adjusting the supply flow rate of the sodium hydroxide aqueous solution by a pH regulator, and the fluctuation range was within a range of 0.2 above and below the set value.
[0168] The obtained composite hydroxide particles included spherical secondary particles with an average particle size of 9.3 μm formed by aggregation of primary particles of 1 μm or less having a void structure, and a void ratio of 51%. In addition, the composition had a molar ratio of nickel to cobalt to manganese of 50:20:30.
[0169] (Cleaning with carbonate)
[0170] The obtained composite hydroxide particles were separated into solid and liquid by a filter press, and a 0.28 mol / L sodium carbonate aqueous solution at 25°C and pH 11.5 (25°C reference) was passed through the filter press at a ratio of 3000 mL relative to 1000 g of the composite hydroxide particles, and then pure water was passed through the filter press for washing. The composition, impurity content, etc. of the washed nickel-cobalt-manganese composite hydroxide (precursor) are shown in Table 1.
[0171] [Manufacturing of positive electrode active material]
[0172] (Mixing process)
[0173] The obtained composite hydroxide, lithium compound, lithium nickel composite hydroxide and lithium hydroxide monohydrate (produced by Wako Pure Chemical Industries, Ltd.) were weighed and mixed so that the molar ratio of the metal components of the lithium nickel composite oxide was Ni:Co:Mn:Li=0.50:0.20:0.30:1.08.
[0174] (Firing process)
[0175] The obtained mixture was calcined in an electric furnace at 900° C. for 9 hours in air atmosphere, and then cooled to room temperature in the furnace and crushed to obtain a positive electrode active material including spherical lithium nickel cobalt manganese composite oxide particles in which primary particles were aggregated.
[0176] [Evaluation of positive electrode active material]
[0177] The positive electrode active material was embedded in the resin and processed by a cross-section polisher. When the cross-section was observed by SEM with a magnification of 5000 times, it was confirmed that the outer shell was formed by sintering the primary particles and the hollow structure inside the outer shell had a hollow part. The porosity of the positive electrode active material obtained from this observation was 58%. The battery was made using the positive electrode active material in the following manner. The physical properties of the precursor are shown in Table 1, and the physical properties of the active material are shown in Table 2. The composition and impurity amount of the obtained positive electrode active material are shown in Table 2.
[0178] (How to make a battery)
[0179] 90 parts by weight of the positive electrode active material powder was mixed with 5 parts by weight of acetylene black and 5 parts by weight of polyvinylidene fluoride, and n-methylpyrrolidone was added to make a paste. The paste was placed on a 20 μm thick aluminum foil so that the weight of the active material after drying became 0.05 g / cm 2 The positive electrode was coated in a manner of , vacuum dried at 120° C., and then punched out into a disk shape with a diameter of 1 cm as a positive electrode.
[0180] Lithium metal was used as the negative electrode, and an equal amount of a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1M LiClO4 as the supporting salt was used as the electrolyte. In addition, a separator made of polyethylene was impregnated with the electrolyte, and a 2032-type button battery was produced in a glove box with an Ar gas atmosphere controlled at a dew point of -80°C. Figure 1 The general structure of a 2032-type button battery is shown. Here, the button battery is composed of a positive electrode (electrode for evaluation) 1 in a positive electrode can 5, a lithium metal negative electrode 3 in a negative electrode can 6, a separator 2 impregnated with an electrolyte, and a gasket 4. The various characteristics (discharge capacity, coulomb efficiency, reaction resistance) of the obtained battery are shown in Table 2.
[0181] (Example 2)
[0182] The positive electrode active material was produced and evaluated in the same manner as in Example 1 except that the sodium carbonate aqueous solution was changed to 0.47 mol / L at pH 11.8 (25° C. standard) and washing was performed at 50 g / L. The evaluation results are shown in Tables 1 and 2.
[0183] (Example 3)
[0184] The positive electrode active material was produced and evaluated in the same manner as in Example 1 except that the sodium carbonate aqueous solution was changed to 1.12 mol / L at pH 12.0 (25° C. standard) for washing.
[0185] (Example 4)
[0186] The positive electrode active material was produced and evaluated in the same manner as in Example 1 except that the metal element molar ratio of the mixed aqueous solution was set to Ni:Co:Mn=60:20:20 in the nucleation step during the production of the precursor.
[0187] The obtained composite hydroxide particles include spherical secondary particles with an average particle size of 9.8 μm formed by agglomerating primary particles of 1 μm or less having a void structure, and the void ratio is 46%. In addition, the molar ratio of nickel, cobalt and manganese is 60:20:20. In addition, the positive electrode active material has a hollow structure or a porous structure, and the void ratio is 49%.
[0188] (Example 5)
[0189] In the nucleation process during the manufacture of the precursor, the molar ratio of the metal elements in the mixed aqueous solution was set to Ni:Co:Mn=40:10:50, and the nitrogen gas was circulated at 5 L / min in such a manner that the oxygen concentration in the space of the reaction tank became 0.2% by volume or less during the nucleation process and the particle growth process. The positive electrode active material was manufactured and evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2.
[0190] The obtained composite hydroxide particles include spherical secondary particles with an average particle size of 10.1 μm formed by aggregation of primary particles of 1 μm or less having a void structure, and the void ratio is 32%. In addition, the molar ratio of nickel to cobalt to manganese is 40:10:50. In addition, the positive electrode active material has a hollow structure or a porous structure, and the void ratio is 27%.
[0191] (Comparative Example 1)
[0192] The positive electrode active material was produced and evaluated in the same manner as in Example 1 except that the sodium carbonate aqueous solution was changed to 0.09 mol / L at pH 11.0 (25° C. standard) for washing.
[0193] (Comparative Example 2)
[0194] The positive electrode active material was produced and evaluated in the same manner as in Example 1 except that the sodium carbonate aqueous solution in Example 1 was replaced with a 1.60 mol / L sodium hydroxide aqueous solution at pH 13.5 (25° C. standard).
[0195] (Comparative Example 3)
[0196] The positive electrode active material was produced and evaluated in the same manner as in Example 1 except that the sodium carbonate aqueous solution was replaced with a 3.39 mol / L sodium hydroxide aqueous solution at pH 14.0 (25° C. standard).
[0197] (Comparative Example 4)
[0198] A reaction tank for continuous crystallization with an overflow pipe on the top was used. The pH at 25°C was maintained at a constant value of 12.5, and the same mixed aqueous solution, ammonia solution and sodium hydroxide solution as in Example 5 were continuously added at a constant flow rate. The average residence time in the tank was set to 10 hours, and the overflowed slurry was continuously recovered, and crystallization was performed by the above method. After the reaction tank reached a state of equilibrium, the slurry was recovered for solid-liquid separation, and the product was washed, filtered and dried to obtain nickel composite hydroxide particles. After calcination, no washing process was performed. Otherwise, the positive electrode active material (lithium nickel cobalt manganese composite oxide) was manufactured and evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2.
[0199] The obtained composite hydroxide particles had no void structure observed, and contained spherical secondary particles with an average particle size of 8.1 μm formed by aggregation of primary particles of less than 1 μm having a dense particle structure, and a porosity of 3%. In addition, its composition, i.e., the molar ratio of nickel to cobalt to manganese, was 0.40:0.10:0.50. In addition, the positive electrode active material had a dense particle structure and a porosity of 2%.
[0200] [Table 1]
[0201]
[0202] [Table 2]
[0203]
[0204] As shown in Table 1, in Examples 1 to 5, the obtained nickel manganese composite hydroxide particles and lithium nickel manganese composite oxide particles have very low impurity content regardless of whether the particles have a multi-void structure (including a porous structure / hollow structure). In addition, the obtained positive electrode active material has excellent battery characteristics such as high capacity, high coulomb efficiency, and low reaction resistance.
[0205] In contrast, in Comparative Examples 1 to 3, the obtained composite hydroxide particles and composite oxide particles had a structure with many voids in the particles and were not sufficiently cleaned, so the amount of impurities was large, the capacity was reduced, and the reaction resistance was also high.
[0206] On the other hand, since the composite hydroxide particles with a dense particle structure are fully cleaned with sodium carbonate in Comparative Example 4, the impurity amount is less than that of the embodiment, and the obtained positive electrode active material has a structure with few voids, so the contact area with the electrolyte is reduced, and the battery characteristics are reduced compared with Example 5 having the same composition ratio.
[0207] Industrial Applicability
[0208] The precursor of the positive electrode active material for a non-aqueous electrolyte secondary battery and the impurity content of the positive electrode active material for a non-aqueous electrolyte secondary battery obtained according to the present invention are greatly reduced. The non-aqueous electrolyte secondary battery using it has a high capacity and excellent coulomb efficiency and reaction resistance. Therefore, it is particularly suitable as a rechargeable and dischargeable secondary battery used in the field of small electronic equipment, and its industrial application potential is very great.
[0209] Description of Reference Numerals
[0210] 1 Positive electrode (evaluation electrode)
[0211] 2 Separator (impregnated with electrolyte)
[0212] 3 Lithium metal anode
[0213] 4 Gasket
[0214] 5. Positive electrode tank
[0215] 6 Negative electrode tank
Claims
1. A method for producing a precursor of a positive electrode active material for a non-aqueous electrolyte secondary battery, characterized in that: The positive electrode active material for the non-aqueous electrolyte secondary battery has a hollow structure or a porous structure, and includes a step of washing nickel-manganese composite hydroxide particles represented by the following general formula (1) with an aqueous carbonate solution having a carbonate concentration of 0.2 mol / L or more. The nickel-manganese composite hydroxide particles include secondary particles aggregated from a plurality of primary particles, and have a void structure inside the particles. Among them, the porosity of the nickel-manganese composite hydroxide particles measured in cross-sectional observation is 15% or more. General formula: Ni x Co y Mn z M t (OH)2···(1) Where 0.2 ≤ x ≤ 0.8, 0 ≤ y < 0.3, 0.07 < z ≤ 0.8, 0 ≤ t ≤ 0.1, x + y + z + t = 1, M is at least one element selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta, and W, and the aqueous carbonate solution is an aqueous solution of at least one selected from potassium carbonate, sodium carbonate, potassium bicarbonate, and sodium bicarbonate. The nickel-manganese composite hydroxide particles are obtained as follows: A mixed aqueous solution containing nickel and manganese, and a metal compound of cobalt and the element M as required, and an aqueous solution containing an ammonium ion donor are supplied to a heated reaction tank. At this time, an aqueous solution of an alkali metal hydroxide in an amount sufficient to keep the reaction solution alkaline is appropriately supplied to the reaction solution, and neutralization crystallization is carried out to obtain the nickel-manganese composite hydroxide particles. In the neutralization crystallization, by controlling the pH value of the reaction solution, a nucleation step for nucleation and a particle growth step for growing the generated nuclei are carried out respectively. Among them, the nucleation step is set in an oxidizing atmosphere with an oxygen concentration exceeding 1% by volume, and the atmosphere is switched from the oxidizing atmosphere to a mixed atmosphere of oxygen and an inert gas with an oxygen concentration of 1% by volume or less in the middle of the particle growth step. Among them, the ammonium ion concentration in the nucleation step and the particle growth step is 3 to 25 g / L.
2. The method for producing a precursor of a positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, characterized in that: The pH of the aqueous carbonate solution is 11.2 or more.
3. The method for producing a precursor of a positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, characterized in that: The washing is carried out in the temperature range of 15 to 50 °C.
4. The method for producing a precursor of a positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, characterized in that: The pH value in the nucleation step is controlled to be 12.0 to 14.0 based on a liquid temperature of 25 °C, and the pH value in the particle growth step is controlled to be 10.5 to 12.5 based on a liquid temperature of 25 °C and a value lower than the pH value in the nucleation step.
5. The method for producing a precursor of a positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 4, characterized in that: The mixed aqueous solution contains at least one of chlorides of nickel, manganese, and cobalt.
6. The method for producing a precursor of a positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein: The sulfate content of the precursor is 0.4% by mass or less, and the sodium content is 0.035% by mass or less.
7. The method for producing a precursor of a positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, characterized in that: The chlorine content of the precursor is 0.1% by mass or less.
8. A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, characterized in that: The manufacturing method includes the following steps: A step of washing nickel-manganese composite hydroxide particles represented by the following general formula (1) with an aqueous carbonate solution having a carbonate concentration of 0.2 mol / L or more, and the aqueous carbonate solution is an aqueous solution of at least one selected from potassium carbonate, sodium carbonate, potassium bicarbonate, and sodium bicarbonate. The nickel-manganese composite hydroxide particles comprise secondary particles aggregated from a plurality of primary particles, and have a void structure inside the particles. Among them, the porosity of the nickel-manganese composite hydroxide particles measured in cross-sectional observation is 15% or more. General formula: Ni x Co y Mn z M t (OH)2···(1) Among them, 0.2 ≤ x ≤ 0.8, 0 ≤ y < 0.3, 0.07 < z ≤ 0.8, 0 ≤ t ≤ 0.1, x + y + z + t = 1, and M is at least one element selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta, and W. The nickel-manganese composite hydroxide particles are obtained as follows: A mixed aqueous solution containing nickel, manganese, and, if necessary, cobalt and the metal compound of the element M, and an aqueous solution containing an ammonium ion donor are supplied to a heated reaction tank. At this time, an aqueous solution of an alkali metal hydroxide in an amount sufficient to keep the reaction solution alkaline is appropriately supplied to the reaction solution, and neutralization crystallization is carried out to obtain the nickel-manganese composite hydroxide particles. In the neutralization crystallization, by controlling the pH value of the reaction solution, a nucleation step for nucleation and a particle growth step for growing the generated nuclei are carried out separately. Among them, the nucleation step is set in an oxidizing atmosphere with an oxygen concentration exceeding 1% by volume, and the atmosphere is switched from the oxidizing atmosphere to a mixed atmosphere of oxygen and an inert gas with an oxygen concentration of 1% by volume or less in the middle of the particle growth step. Among them, the ammonium ion concentration in the nucleation step and the particle growth step is 3 - 25 g / L. A mixing step of mixing the washed nickel-manganese composite hydroxide particles with a lithium compound to obtain a lithium mixture; and A firing step of firing the lithium mixture in an oxidizing atmosphere in the range of 800 - 1100 °C to obtain a lithium nickel manganese composite oxide. The positive electrode active material contains a lithium nickel manganese composite oxide represented by the following general formula (2) and having a hollow structure or a porous structure. General formula: Li a Ni x Co y Mn z M t O2···(2) Among them, 0.95 ≤ a ≤ 1.20, 0.2 ≤ x ≤ 0.8, 0 ≤ y < 0.3, 0.07 < z ≤ 0.8, 0 ≤ t ≤ 0.1, x + y + z + t = 1, and M is at least one element selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta, and W.
9. A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, characterized in that: The manufacturing method includes the following steps: A step of washing the nickel-manganese composite hydroxide particles represented by the following general formula (1) with an aqueous carbonate solution having a carbonate concentration of 0.2 mol / L or more. The aqueous carbonate solution is an aqueous solution of at least one selected from potassium carbonate, sodium carbonate, potassium bicarbonate, and sodium bicarbonate. The nickel-manganese composite hydroxide particles comprise secondary particles aggregated from a plurality of primary particles, and have a void structure inside the particles. Among them, the porosity of the nickel-manganese composite hydroxide particles measured in cross-sectional observation is 15% or more. General formula: Ni x Co y Mn z M t (OH)2···(1) Among them, 0.2 ≤ x ≤ 0.8, 0 ≤ y < 0.3, 0.07 < z ≤ 0.8, 0 ≤ t ≤ 0.1, x + y + z + t = 1, and M is at least one element selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta, and W. The nickel-manganese composite hydroxide particles are obtained as follows: A mixed aqueous solution containing nickel, manganese, and, if necessary, cobalt and the metal compound of the element M, and an aqueous solution containing an ammonium ion donor are supplied to a heated reaction tank. At this time, an aqueous solution of an alkali metal hydroxide in an amount sufficient to keep the reaction solution alkaline is appropriately supplied to the reaction solution, and neutralization crystallization is carried out to obtain the nickel-manganese composite hydroxide particles. In the neutralization crystallization, by controlling the pH value of the reaction solution, a nucleation step for nucleation and a particle growth step for growing the generated nuclei are carried out separately. Among them, the nucleation step is set in an oxidizing atmosphere with an oxygen concentration exceeding 1% by volume, and the atmosphere is switched from the oxidizing atmosphere to a mixed atmosphere of oxygen and an inert gas with an oxygen concentration of 1% by volume or less during the particle growth step. Among them, the ammonium ion concentration in the nucleation step and the particle growth step is 3 - 25 g / L. A calcination step of calcining the washed particles in an oxidizing atmosphere at 150 - 1000 °C. A mixing step of mixing the calcined nickel-manganese composite hydroxide particles with a lithium compound to obtain a lithium mixture; and A firing step of firing the lithium mixture in an oxidizing atmosphere in the range of 800 - 1100 °C to obtain a lithium nickel manganese composite oxide. The positive electrode active material contains a lithium nickel manganese composite oxide represented by the following general formula (2) and having a hollow structure or a porous structure. General formula: Li a Ni x Co y Mn z M t O2···(2) Among them, 0.95 ≤ a ≤ 1.20, 0.2 ≤ x ≤ 0.8, 0 ≤ y < 0.3, 0.07 < z ≤ 0.8, 0 ≤ t ≤ 0.1, x + y + z + t = 1, and M is at least one element selected from Mg, Ca, Ba, Sr, Al, Ti, V, Cr, Zr, Mo, Hf, Ta, and W.
10. The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 8 or 9, characterized in that: The lithium compound is at least one selected from the group consisting of lithium hydroxide, hydroxyoxide, oxide, carbonate, nitrate, and halide.
11. The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 8 or 9, characterized in that: The sulfate content of the positive electrode active material is 0.4% by mass or less, and the sodium content is 0.035% by mass or less.
12. The method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 8 or 9, characterized in that: The chlorine content of the positive electrode active material is 0.05% by mass or less.
Citation Information
Patent Citations
Manganese-nickel mixed hydroxide particle
JP2004210560A
Nickel composite hydroxide and process for producing same, positive active material for nonaqueous-electrolyte secondary battery and process for producing same, and nonaqueous-electrolyte secondary battery
WO2012169274A1
Composition precursor for aluminum-containing lithium transition metal oxide and process for preparation of the same
CN101027805A
Nickel-manganese composite hydroxide particles, method for producing same, positive electrode active material for nonaqueous electrolyte secondary batteries, method for producing said positive electrode active material, and nonaqueous electrolyte secondary battery
CN102884659A